Perjanjian Hipotek Kapal (Studi Komparatif antara Indonesia dan Amerika Serikat) - Syarifah Zahra Al Haddar; Djoni Sumardi Gozali (AHKAM, 2026)
Although the regulation of ship mortgages has received attention in various maritime law studies in Indonesia, research that specifically compares Indonesia’s ship mortgage system with the United States preferred ship mortgage regime to evaluate its implications for legal certainty for creditors remains limited. This study aims to analyze the similarities and differences in the regulation of ship mortgages in Indonesia and the United States and to evaluate the implications of differences in registration mechanisms, claim priority, and enforcement for legal certainty in maritime financing. This study used a qualitative approach with a normative legal research type and a comparative design. Data were obtained through library research on primary, secondary, and tertiary legal materials, including the Indonesian Civil Code, the Indonesian Commercial Code, Law Number 17 of 2008 concerning Shipping, the Ship Mortgage Act, the Commercial Instruments and Maritime Liens Act (CIMLA), as well as relevant maritime law doctrines and literature. The data were analyzed qualitatively through statutory, conceptual, and comparative legal approaches. The results show that Indonesia and the United States both recognize ships as objects of proprietary security rights and require mortgage registration, but differ fundamentally in their registration systems, regulation of claim priority, and enforcement mechanisms. The United States system provides stronger legal certainty through an integrated federal registration system, clearer regulation of claim priority, and an effective in rem action mechanism, whereas the Indonesian system still faces regulatory fragmentation and administrative obstacles. The conclusion of this study emphasizes the importance of reformulating ship mortgage regulation in Indonesia through regulatory harmonization, strengthening the national registration system, and improving enforcement mechanisms. These findings contribute to the development of studies on proprietary security law and maritime law and provide practical recommendations for policymakers in strengthening legal certainty in national maritime financing.